Analysis of Evidence in the CAS 2019/A/6636 BC Arsenal v. Russian Basketball Federation Case and Prediction of the Position of CAS in the Case - D. A. Afanasev (Теоретическая и прикладная юриспруденция)
The subject of the article is the question of responsibility of persons for match-fi activities. The issue of probable assessment of evidence in CAS 2019/A/6636 is being considered. Predicting the CAS position is based on established Arbitration practice. The parties positions are modeled based on information available in open sources.